Investigation of sources and atmospheric transformation of carbonaceous aerosols from Shyamnagar, eastern Indo-Gangetic Plains: Insights from δ13C and carbon fractions. (June 2023) - Singh, Gyanesh Kumar; Qadri, Adnan Mateen; Paul, Debajyoti; Gupta, Tarun; Mukherjee, Sauryadeep; Chatterjee, Abhijit
Abstract: This study reports the chemical characterization of the carbonaceous component of PM2.5 (particulate matter with aerodynamic diameter ≤2.5 μm) collected over a year-long campaign from a regional site in Shyamnagar, West Bengal, in the Indo-Gangetic Plains (IGP), India. The carbonaceous fractions (elemental and organic carbon), mass concentrations, and stable carbon isotopic composition ( δ 13 C value) of aerosols were measured and utilized to characterize the sources and understand the atmospheric processing of aerosols. Cluster analysis, Potential Source Contribution Function (PSCF) modeling, and fire count data were analyzed to decipher the pattern of air masses, source contributions, and extent of burning activities. The PM2.5 mass concentrations were significantly higher during winter (168.3 ± 56.3 μg m −3 ) and post-monsoon (109.8 ± 59.1 μg m −3 ) compared to the monsoon (29.8 ± 10.7 μg m −3 ) and pre-monsoon (55.1 ± 23.0 μg m −3 ). Organic carbon (OC), elemental carbon (EC), and total carbon (TC) concentrations were also several factors higher during winter and post-monsoon compared to monsoon and pre-monsoon. The winter and post-monsoon experienced the impact of air masses from upwind IGP. On the other hand, long-range transported air masses from the South-West direction dominated during monsoon and pre-monsoon, which are also relatively cleaner periods. The average δ 13 C during post-monsoon and winter was ∼1‰ higher compared to monsoon and pre-monsoon. The vehicular exhaust and biomass/biofuel burning contributed dominantly in winter and post-monsoon. In comparison, lower δ 13 C in pre-monsoon and monsoon might be attributed to the dominance of biomass/biofuel combustion. Photochemical-induced aging of the anthropogenic aerosols resulted in a higher δ 13 C of TC in winter and post-monsoon, whereas the mixing of different local sources in pre-monsoon and monsoon resulted in lower δ 13 C values. These findings benefit policymakers in strategizing proper and effective management of biomass/biofuel burning in the IGP to minimize air pollution. Graphical abstract: Image 1 Highlights: PM2.5 concentration in Shyamnagar was higher during winter and post-monsoon. Mean δ 13 CPM2.5 in winter and post-monsoon was higher than pre-monsoon and monsoon. Higher δ 13 CPM2.5 in winter and post-monsoon is attributed to photochemical aging. Lower δ 13 CPM2.5 in pre-monsoon and monsoon was due to mixing and wet scavenging. Winter and post-monsoon showed dominance of exhaust and biomass burning emissions.